Optimum design of stiffened composite cylindrical shells with a cutout for maximum buckling strength - Değer, Sezer. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2022., 2022)
Thin-walled composite cylindrical shells have low resistance to buckling and out-of-plane deformations. Introducing a cutout to these structures reduces the load-carrying capacity of such structures drastically. One effective way to recover the load- carrying capacity lost due to a hole is to place stiffeners around the hole. The objective of this study is to find an optimum reinforcement for thin-walled composite cylindrical shells with a cutout to maximize the buckling load and minimize the additional mass due to the reinforcement. A finite element model of a thin-walled composite cylinder with an opening is created and validated using the results of an experimental and numerical study. Then hat-type stiffeners are applied around the cutout. A parametric study is carried out to determine the effect of each stiffener parameter on the buckling strength of the structure and to choose suitable upper and lower limits for optimization. A modified simulated annealing algorithm is used to find the global optimum reinforcement design. Both the FEA and the optimizations are carried out using ANSYS Parametric Design Language (APDL). In the first step , the optimum designs are obtained for stiffeners placed in the axial direction at certain distances to the center of the cutout by varying only the cross-sectional parameters and the length of the stiffener. In the second stage, the distance to the hole center is also optimized. Finally, using the optimum stiffener dimensions optimization is performed by placing additional small stiffeners on the top and bottom of the cutout. Significant improvements are achieved by using optimum stiffener designs. The most effective parameters are found to be the stiffener length, stiffener distance to the center of the opening and stiffener height.
Keywords: Roofs, Shell -- Design and construction.; Buckling (Mechanics) -- Mathematical models.